Syariah compliance in retail: concept and design - Khalil, Khainina; Ahmad Noorhani, Nur Maizura; Mustapha, Arniatulaiza; Zulkifli, Fatimah Najah (Universiti Teknologi MARA, Kelantan, 2018)
Malaysia is currently experiencing a new transformation which is adopting Islamic concept and principles in retailing as mentioned by Abu Bakar and Hussin (2013) [2; 20] or by truthful says, is phasing of the enhancement of value added in life. The Islamic concepts comprise the Syariah compliance elements which is the religious law that controls religious rituals and also the aspects of everyday life in Islam. Looking at retail designing views, sadly the essence of culture and identity of Muslims in Malaysia is decreasing vastly due to development and modernization. Designers compete to produce contemporary and unique spaces and ignored the importance of implementing the Islamic values and principles in design. Therefore, this paper is to determine the Syariah compliance elements to be applied in retail design. This paper also reviews the Islamic concept and principles in establishing the elements in retail design according to Syariah compliance. Consequently, for this particular objective, the observation of two (2) major retail store has been done to analyzed the elements providedby comprehensive literature reviews. As a result, by adopting the whole Islamic concept and principles into retail design will ensure the space and activities potential to be used up to maximum that will benefit the consumer.